Parents’ personality disorders as predictor of substance and alcohol use in children and adolescents - Mohammadi, Mohammad Reza; Hojjat, Seyed Kaveh; Mostafavi, Seyed Ali; Khaleghi, Ali; Hooshyari, Zahra; Ahmadi, Nastaran Ahmadi; Kaviyani, Faezeh; Norozi Khalili, Mina (Technium Social Sciences Journal, 2020)
This study investigated how the parents’ personality disorders may be related to substance and alcohol in children and adolescents. 277 children and adolescents (aged 6 to 18) with diagnosis of substance and alcohol use and 362 parents participated in this study. The diagnosis of substance and alcohol use was made using the K-SADS-PL interview. The parents were also surveyed for their personality assessed with Millon Clinical Multiaxial Inventory. The results showed that the paranoid personality disorder in father and borderline personality disorder in mother increase the chance of substance and alcohol use in children. The findings suggest that in defining preventive programs for substance and alcohol use, the personality characteristics of the parents need to be taken into account